Complete mitochondrial genome of Cynopterus sphinx (Pteropodidae: Cynopterus). (2nd November 2015) - Li, Linmiao; Li, Min; Wu, Zhengjun; Chen, Jinping
Abstract: We have characterized the complete mitochondrial genome of Cynopterus sphinx (Pteropodidae: Cynopterus ) and described its organization in this study. The total length of C. sphinx complete mitochondrial genome was 16, 895 bp with the base composition of 32.54% A, 14.05% G, 25.82% T and 27.59% C. The complete mitochondrial genome included 13 protein-coding genes, 22 tRNA genes, 2 rRNA genes (12S rRNA and 16S rRNA) and 1 control region (D-loop). The control region was 1435 bp long with the sequence CATACG repeat 64 times. Three protein-coding genes (ND1, COI and ND4) were ended with incomplete stop codon TA or T.